PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN POLA SPASIAL GEOGRAFI - Yulia Prasetiyowati; Trisnaningsih Trisnaningsih; Pujiati Pujiati (Jurnal Studi Sosial / Journal of Social Studies, 2017)
This research aims to improve the understanding of the spatial patterns of Geography students in the learning process by using a model of Discovery Learning. The research is the research action class. This research activity was carried out as many as three cycles, each cycle consisting of the planning stages, action, observation, and reflection, which aims to improve the quality of learning. The subject of the research are all students in class XII IPS1 YASMIDA Ambarawa high school year lessons 2015-2016 as much as 19 students. Data collection tool using the pattern of spatial understanding observation sheet Geography and test the results of the study in the form of multiple choice question. Data from the results of observation and formative tests in each cycle is fundamental or material improvements in the next cycle. The results showed that: there is a growing understanding of the spatial patterns of Geography students seen from increasing student learning outcomes at each cycle after use of Discovery Learning in learning Geography.Penelitian ini bertujuan untuk meningkatkan pemahaman pola spasial Geografi siswa dalam proses pembelajaran dengan menggunakan model Discovery Learning. Penelitian ini adalah penelitian tindakan kelas. Kegiatan penelitian ini dilaksanakan sebanyak tiga siklus, tiap siklus terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi, yang bertujuan untuk memperbaiki kualitas pembelajaran. Subjek penelitian adalah seluruh siswa di kelas XII IPS1 SMA YASMIDA Ambarawa Tahun Pelajaran 2015-2016 sebanyak 19 siswa. Alat pengumpulan data menggunakan lembar pengamatan pemahaman pola spasial Geografi dan tes hasil belajar yang berupa soal pilihan ganda. Data dari hasil observasi dan tes formatif di setiap siklus menjadi dasar atau bahan perbaikan pada siklus berikutnya. Hasil penelitian menunjukkan bahwa: terdapat peningkatan pemahaman pola spasial Geografi siswa yang terlihat dari meningkatnya hasil belajar siswa disetiap siklus setelah penggunaan model Discovery Learning pada pembelajaran Geografi.Kata Kunci: Pemahaman Pola Spasial Geografi, Hasil Belajar, Discovery Learning .